“Estrategia de intervención nutricional para mejorar los hábitos alimentarios en pacientes infectados con el virus inmunodeficiencia humana (VIH) que reciben tratamiento antirretroviral de gran actividad (Targa) en el hospital II-2 Tarapoto. Junio-Diciembre 2015” - Farro Roque, Maria Elena (2015)
This research work in order to design and implement a strategy Nutritional lntervention to improve the eating habits of patients infected with human immunodeficiency virus (HIV) receiving antiretroviral therapy (HAART) treated at the Hospital 11 - 2 Tarapoto. June to December 2015. The population consisted of 390 patients infected with HIV I AIDS who attended the clinic Nutrition during the study period. The research was quantitative, experimental, prospective, cross-sectional, based on a sample of 144 cases. the pre-experimental design was used with one group pre and post test since the intervention strategy was developed exclusively for research. The results were: prevalence of infected patients between 20 - 39 years old (81.2%), single marital status (51.4%); secondary level education (37.5%) and Catholic (71.5%) religion. 56.0% were mate, occupation housewife (33.3%) and students (25.0%). 46.5% have a normal nutritional status prone to thinness grade 1 (31.3%) and overweight (13.2%). Habits and dietary habits was most common food rich in carbohydrates + protein (31.3%), food rich in protein (21.5%) and food rich in vitamins (20.8%). 74.3% have harmful habits like frequent consumption of stimulating beverages (tea, coffee); 26.4% have food intolerance; the frequency of food consumption is 3 times a day (88%). 51.4% are in a state of normal nutrition according to clinical evaluation, prone to lost weight with Dx. malnutrition (21.5%). The assessment of nutritional status before and after application of the nutritional strategy, reporting percentage differences. the chi-square test nonparametric read with a significance leve! of <0.05 was applied, obtaining a value X2 = 148.625; p = 0.00000, accepting the hypothesis proposed investigation.